The Influence of Organizational Culture and the Physical Work Environment on Teacher Work Discipline at XYZ Vocational High School in Cimahi - Revina Purwanti; Khaerul Rizal Abdurrahman (LP2M IAIN Palopo, 2026)
In improving the performance of an institution, teacher work discipline plays a key role in achieving high-quality education. Ensuring good teacher work discipline involves fostering strong adherence among teachers to the values upheld by the institution; furthermore, providing adequate work facilities for teachers as they carry out their duties will encourage them to comply with the rules and regulations established by the institution. However, observations at SMK XYZ Cimahi indicate that the institution’s values have not yet been fully implemented and the work facilities provided by it are not yet optimal, which is suspected to affect work compliance. The aim of these studies to identify the influence of the organizational and workplace environment on teachers’ work discipline at XYZ Vocational High School in Cimahi, both individually and collectively. The study employed a quantitative methods approach with data analysis, and specifically multiple regression analysis using SPSS 26 software, which combines descriptive quantitative methods and associated quantitative methodology. Data were collected through the distribution of questionnaires. The sample consisted of 45 teachers at SMK XYZ Cimahi. The results show that organizational and workplace culture each have a partial effect on teacher discipline. Furthermore, organization's cultures and the workplace environment simultaneously influence work discipline; this study indicates that organization's culture and the workplace environment on work discipline fall into the category of high or strong influence. This suggests that the more strongly teachers uphold the values championed by the institution and the more adequate the facilities provided, the higher their level of adherence to applicable regulations and guidelines.